Socioeconomic Determinants of Psychotropic Drug Utilization at a Tertiary Hospital in Dhaka City - Any, Omma Hafsa; Parveen, Feroza; Sultana, Rezina; Iqbal, Md Jalal Uddin (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Mental illness is the most neglected disease in Bangladesh with a large number of people suffering from different types of mental illness. Objectives: The purpose of the present study was to find out socioeconomic determinant of psychotropic drug in tertiary level hospital. Methodology: This cross sectional descriptive study was carried out at the Sir Salimullah Medical College and Mitford Hospital (SSMC & MH), Dhaka from the period of July 2009 to June 2010. All the patients attended at psychiatry outpatient department were included as study population. The collected data include socio-demographic details by depth interview; Informed consent was obtained verbally from the patient or legal guardian. The psychiatry out-patient departments are selected because both rural and urban population of different classes and different socio-economic status daily come to these out-patient departments for their treatment purposes. They predominantly represent poor rural and urban population. Result: A total 300 patients were included in this study. Out of 300 patients158 patient (52.66%) were female, most of the patients were age group 18-27 years, 108(36%) patient were house wife. Schizophrenia and other psychotic disorder are most common complaint among the patient attending the psychiatry OPD, 293(97.67%) patient came from rural areas, 175(58.33%) patient were married. Most of the patients are illiterate. It was observed that less educated, illiterate, housewife, unemployed and lower income group of patients generally attend psychiatry out-patient department. Conclusion: In conclusion less educated, illiterate, house wife, unemployed and lower income group of patients generally attend psychiatry out-patient department. J Shaheed Suhrawardy Med Coll, 2015; 7(1):10-13